(3OjhGf GHf Yfjfs - (3GHf Yfjf , eMeO Hf fUQ Gddg Hf ecGQe Hf GdMSf GdRQYj, TQa GdOjf CHh GdeMGSf,J (B630 (3g` s ((3eMeO Gejf GdGScOGQi s)
(3ChdgG (B:s
(3GdMeO ddg GdefYe Ydi NdbI bGd GdTjN hbOQ KHJ ai Chd GdOjhGf eG CJi Hg GdeOGFM ddedhc Ydi bOQ eG jHdge ef GdhRQGA hZjQge eGPG Ydi Wja GdGMHI dh SQi hYdjge dh SGeMhfi HGdcQi s
(3BNQgG (B:s
(3hEPG YcSJ GdLeY cGf GSeG def CaYGdI eTghQI ai GdShOQ fLR GdOjhGf HYhf Gddg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B125 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B79s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs